‘Maiduguri’ as Parable of Postcolonial Condition: Interrogating the Contexts of Patrick Oguejiofor’s Maiduguri Requiems - Udoinwang, David Ekanem; Enukora, Elizabeth N. (NIU Journal of Social Sciences, 2024)
In Patrick Oguejiofor’s collection of poems, Maiduguri Requiems , ‘maiduguri’ is metaphorised as a weird landscape noted for endless lamentations, especially over the horror of terror, instability and permissive tragedies of human disaster and disillusionments. The poems resonate a disruptive parable of postcolonial African encounters that invite critical attention. This work adopts a qualitative method of analysis in which the collection is read purposively and examined critically, relying on trauma theory and post colonialism as theoretical parameters. The selected entries are examined towards situating the connections between poetic imagination and socio-political and historical realities of a nation that has remained atomistic, ill at ease with itself and as citadel of terror, banditry and appalling contradictions. The analysis unravels ‘maiduguri’ beyond the assumed locale but as symptomatic of a nation that held great promise at independence but has continued to drift many decades after independence till deep into the 21th century, when others are growing at great speed on the scale of living standards and meaningful progress. The work concludes that the postcolony has remained too long at the brinks of human tragedy, and must exert as much energy as possible to brace up to the reality of postmodernity through systemic repair and reorientation in every ramification. Keywords: Maiduguri, the postcolony, extremism, human disaster, lamentation, Oguejiofor.